Sustainability reporting in the construction sector: trends, models, metrics and challenges towards achieving the SDGs - Ludivia Hernandez Aros; Aracelly Buitrago Mejia; Henry Alberto Binns Hernández; Fernando Gutierrez Portela (Research in Globalization, 2025)
The practice of sustainability reporting in the construction sector has been established to promote responsible practices and align the sector’s activities with the Sustainable Development Goals (SDGs). The present study is an SLR, the results of which are based on 204 articles extracted from Scopus and Web of Science, and analysed using bibliometric techniques such as VOSViewer, applying the SALSA framework. The objective of the present study is to address the existing gap in the literature on sustainability information in the construction sector through a systematic review, with the aim of identifying trends, research trajectories and relevant emerging topics. The identification of trends in authors, countries and keywords is complemented by an analysis of the most used frameworks and/or models, including the GRI and the ESG approach. Moreover, the most influential metrics comprise energy efficiency, carbon footprint and resource use. The extant literature identifies barriers (costs, lack of regulation, cultural resistance) and enablers (regulations, stakeholder pressure, reputational benefits) in the adoption of these reports. Finally, it emphasises potential avenues for future research, including the standardisation of indicators, the integration of emerging technologies, and the development of strategies to enhance the sector’s impact on the SDGs. The study provides an integrative overview of the current state of knowledge, offering theoretical, practical, and managerial implications for sustainable and strategic construction.